Oxide Semiconductors: Arc‐Melting to Narrow the Bandgap of Oxide Semiconductors (Adv. Mater. 16/2015). (April 2015) - Ou, Gang; Li, Dongke; Pan, Wei; Zhang, Qinghua; Xu, Ben; Gu, Lin; Nan, Cewen; Wu, Hui
<x xml:space="preserve">Abstract</x> W. Pan, H. Wu, and co‐workers highlight engineering the bandgap of oxides through rapid arc‐melting on page 2589. Rich defects are implanted by a fast melting and cooling process, resulting in narrowed bandgap and enhanced optical absorption in a series of oxides including ZnO, Y2O3, ZrO2, Nb2O5, In2O3, SnO2, CeO2, Cu2O, and WO3. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>